Not all ‘Coolies’ are the same: South African Indians and the performance of comedy in articulating identity in post-apartheid South Africa - Sana, Vidhya (My University, 2020)
Post-Apartheid South Africa saw many communities attempt to negotiate anxieties of identity and belonging in the new cultural landscape that came along with democracy. The South African Indian community, in particular, has navigated issues of identity and belonging in a society largely informed by a black/white binary. They have done so in various ways. The rise of comedic acts stemming from this community suggests that comedy is one avenue with which South African Indians are able to perform their identities. In all, this project considers the South African Indian community’s rejection of the notion that they are not a diaspora of India, but rather fully-fledged South Africans with no yearning for a mythical ‘home’. Comedy, in its proliferation in South Africa, and as a useful medium to be able to speak about issues that are considered taboo, allows for the gathering of a rigorous data set to be able to explore issues of identity and belonging in post-Apartheid South Africa. The study considers the works of Riaad Moosa, Peru and Bala, Karou Charou and the movie ‘Keeping up with the Kandasamy’s’. Through an analysis of the various themes that these comedic acts preoccupy themselves with, inferences can be made about the ways in which the South African Indian community addresses issues of identity and belonging in South Africa. Tropes of religion, food and cultural symbols, such as dress and Bollywood, reveal that some members of the community articulate acts of cultural memory in an attempt to create a sense of belonging within the community. The traditional notions of patriarchy that governed Apartheid South Africa and Indian cultures(and still continue to govern), are maintained within the community through notions of gender roles, sexual morality and the maintenance of traditional notions of masculinity, femininity and sexuality. Finally, the increasing influence of neoliberal capitalism has meant that some performances of comedy have adopted an excessive character (the figure of the ‘Charou’ in particular),along with exploring anxieties of excess and the freedom to consume in their themes. The project ultimately explores how South African Indians see themselves in relation to the global Indian diaspora, in relation to other South Africans, and in relation to each other within the community through the exploration of these themes
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Media Studies, Department of Media Studies, Faculty of Humanities, University of the Witwatersrand, 2020